2007
DOI: 10.1136/jnnp.2006.099077
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of secondary degeneration following subcortical infarction using diffusion tensor imaging

Abstract: Background: Secondary degeneration of the pyramidal tract distal to the primary lesion after a stroke has been detected by some studies using diffusion tensor imaging (DTI) but its potential clinical significance and the degeneration of the fibre tract proximal to the primary lesion have received little attention. Methods: Twelve patients underwent DTI on the 1st, 4th and 12th week following a subcortical infarct involving the posterior limb of the internal capsule, and 12 age and sex matched controls underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
105
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 21 publications
(21 reference statements)
12
105
0
2
Order By: Relevance
“…1 In addition, longitudinal studies have demonstrated that a progressive decrease of FA occurs along the pyramidal tract in the cerebral peduncle below the primary lesion. 2,3 In accordance with previous studies, we found that FA of the ipsilesional brain stem significantly decreased in both CPH and PPH compared with healthy controls, and FA also significantly decreased in CPH compared with PPH. Furthermore, FA correlated positively with Fugl-Meyer Assessment scores (handϩwrist) across all patients.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…1 In addition, longitudinal studies have demonstrated that a progressive decrease of FA occurs along the pyramidal tract in the cerebral peduncle below the primary lesion. 2,3 In accordance with previous studies, we found that FA of the ipsilesional brain stem significantly decreased in both CPH and PPH compared with healthy controls, and FA also significantly decreased in CPH compared with PPH. Furthermore, FA correlated positively with Fugl-Meyer Assessment scores (handϩwrist) across all patients.…”
Section: Discussionsupporting
confidence: 80%
“…A case of pontine infarction with retrograde degeneration has been detected and confirmed postmortem, 15 and the progressive reduction of FA value in the fiber tract above the initial infarction also reflects retrograde degeneration proximal to the primary lesion. 2 Two types of fiber tracts have been proposed in previous studies: 1) one is from neurons in the motor cortex, descending from the subcortex to the spinal cord and production pyramidal tract; and 2) the other is derived from relay nuclei in the thalamus that consist of basal ganglia-thalamocortical circuits. 2,[16][17][18] Moreover, Alexander et al (1986) 16 suggested that the 5 basal ganglia-thalamocortical circuits are organized in parallel and that each circuit engages specific regions of the cerebral cortex involving the motor cortex, somatosensory cortex, supplementary motor area, cingulate motor cortex, and superior temporal gyrus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 It has been reported that FA, which is a quantitative index of the directional anisotropy of water molecular diffusion derived from the diffusion tensor, is an effective measure of fiber integrity. 3 Decreases in FA have been found in the affected tracts at infarct regions and regions with wallerian degeneration.…”
mentioning
confidence: 99%